Knowledge, information and creativity support systems : recent trends, advances and solutions : selected papers from KICSS '2013, 8th International Conference on Knowledge, Information, and Creativity Support Systems, November 7-9, 2013, Kraków, Poland /: recent trends, advances and solutions : selected papers from KICSS '2013, 8th International Conference on Knowledge, Information, and Creativity Support Systems, November 7-9, 2013, Kraków, Poland. (2016) - Unknown
No abstract available